Improved medical protective clothing comfort for medical staff facing high-intensity infectious diseases - Cheng-teng Jiang; Cheng-teng Jiang; Dong-yu Chen; Rong Zhang; Fei Ren; Han-wen Zheng; Yuan Yue; Shi-quan Xing; Chuang Nie; Jian-wen Gu (Frontiers in Public Health)
IntroductionDuring outbreaks of respiratory infectious diseases such as the COVID-19 pandemic, healthcare workers are frequently required to wear medical protective clothing (MPC) for prolonged periods. Traditional MPC, however, prioritizes protective efficacy while neglecting wearer comfort. Its poor air permeability can induce physical fatigue and dehydration in medical staff during extended use, thereby exacerbating their burden when managing severe infectious diseases. Accordingly, this study aims to enhance the comfort of existing MPC, which holds significant implications for improving the working conditions of medical staff in protracted infectious disease scenarios.MethodsTo address this challenge, a novel integrated MPC was developed through the recombination of mainstream materials. A total of 208 volunteers participated in the experiment, yielding 196 valid data points (81 males and 115 females).ResultsComparative assessments revealed that the new MPC enhanced air permeability to 120 mm/s, reduced sweating by 30%, decreased skin temperature by 1.2°C, and lowered the incidence of skin maceration by 45%. Furthermore, it shortened donning and doffing time from 5 to 3 minutes.DiscussionThese findings offer a practical strategy for improving MPC comfort without compromising its protective capabilities.